The Boundary of Recruitment: A Response. Issue 1 (2nd January 2016) - Kendrick, Kobin H.; Drew, Paul
ABSTRACT: In their commentaries, both Heritage (2016/this issue) and Zinken and Rossi (2016/this issue) provide some context for our concept of and approach to recruitment in terms of previous research into requesting and offering. In doing so, they usefully consider what might be the "boundaries" of recruitment—what might be included and what might not be included or treated as recruitment. We respond here to their suggestions concerning these boundaries.